2017
DOI: 10.1108/mf-10-2016-0291
|View full text |Cite
|
Sign up to set email alerts
|

The Sarbanes-Oxley Act and corporate acquisitions

Abstract: Purpose The purpose of this paper is to analyze and compare the performance of corporate acquisitions between the pre- and post-SOX periods, using both short-term and long-term analyses. Design/methodology/approach The sample includes 9,463 mergers and tender offers undertaken by publicly traded US firms between 1996 and 2009. The authors used the standard event study methodology for short-term performance analysis; Berkovitch and Narayanan (1993) method to identify merger motives; and standard benchmark adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
28
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(36 citation statements)
references
References 55 publications
7
28
1
Order By: Relevance
“…In this paper we find compelling evidence that despite continued positive abnormal returns for acquirers of private targets, these positive returns have decreased significantly in the post-SOX period. This is in sharp contrast to the higher abnormal returns observed for acquirers of public targets in the post-SOX period (Bhabra and Hossain, 2017a, 2017b.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…In this paper we find compelling evidence that despite continued positive abnormal returns for acquirers of private targets, these positive returns have decreased significantly in the post-SOX period. This is in sharp contrast to the higher abnormal returns observed for acquirers of public targets in the post-SOX period (Bhabra and Hossain, 2017a, 2017b.…”
Section: Discussioncontrasting
confidence: 79%
“…We also compute announcement CARs for subsamples since deal and firm‐specific factors have been known to affect acquirer returns. For example, acquirers in cash‐only deals perform better (Datta et al , 2001; Bhabra and Hossain, 2017a). In addition, Moeller et al (2004) find that acquirer excess returns around acquisition announcement vary with firm and deal size.…”
Section: Methodsmentioning
confidence: 99%
“…While one interpretation could be that a reduction in agency conflicts post-SOX reduces over-investment and hence the increase in marginal value of capital expenditure (see, e.g. Bhabra and Hossain, 2017b), another possibility is that a possible reduction in the premium demanded by investors, thus reducing the discount rate applied to investment projects and consequently increasing the contribution that capital expenditures make to firm value. There is no evidence to suggest an increase in risk aversion or of SOX imposing excessive costs for the full sample, unless one believes that capital expenditures forgone following an increase in the perceived discount rate or because of a lack of funds due to compliance costs were actually value destroying in the first place.…”
Section: Resultsmentioning
confidence: 99%
“…Our sample consists of successful public merger and tender offers from May 2003 to December 2012 obtained from the SDC Platinum Database. We start our sample period in 2003, as the Sarbanes–Oxley Act (SOX) was passed in 2002, and previous research (e.g., Egan 2005; Masulis, Wang, and Xie 2007; Bhabra and Hossain 2017a, 2017b, 2018) has shown that SOX influenced M&A market activity. We identify the financial crisis period as March 2007 to February 2009, as noted by the Federal Reserve Bank of St. Louis in USA Today .…”
Section: Methodsmentioning
confidence: 99%